Representasi Nilai Pendidikan Lingkungan Novel Jejak Balak Karya Ayu Werilang (2023): Kajian Ekokritik - Nisma, Nisma (Institut Teknologi Sepuluh Nopember, 2025)
This study is a qualitative research with a descriptive approach that aims to examine the value of environmental education in the novel Jejak Balak by Ayu Werilang (2023). The primary data source is the novel’s text, focusing on environmental phenomena, while secondary sources include journals, books, and previous studies relevant to ecocriticism and environmental education. Data collection techniques involve documentation and note-taking from the novel and other written sources. The data were analyzed using Greg Garrard’s (2004) ecocritical approach, which consists of six main concepts: pollution, wilderness, apocalypse, dwelling, animals, and earth. The research findings indicate that Jejak Balak represents environmental education values through these six aspects in line with Garrard’s theory. The novel highlights issues such as forest conservation, criticism of environmental exploitation and irresponsible corporations, the role of local wisdom in environmental sustainability, the ecological impact of deforestation, animal symbolism in human-nature relationships, and the role of characters as environmental change agents. As an ecologically themed literary work, the novel serves as an educational and reflective medium, emphasizing human responsibility in maintaining ecological balance and raising awareness of environmental issues